Low-voltage, simple WO3-based electrochromic devices by directly incorporating an anodic species into the electrolyte. Issue 46 (9th November 2016) - Bae, Jaehyun; Kim, Haekyoung; Moon, Hong Chul; Kim, Se Hyun
Abstract : Low-voltage tungsten trioxide (WO3 )-based electrochromic devices (ECDs) are successfully demonstrated. Abstract : Low-voltage tungsten trioxide (WO3 )-based electrochromic devices (ECDs) are successfully demonstrated. In contrast to conventional ECDs based on metal oxides, we directly introduce ferrocene (Fc) as an anodic species into the electrolyte layer. Accordingly, ECDs in this work do not require secondary electrochromic materials on the counter electrode, and thus device configuration and the fabrication process are simplified. The coloration and bleaching behaviors of the device occur in the voltage range of 0 V to −1.5 V with a maximum transmittance contrast (Δ T max ) of ∼52% at 700 nm. In addition, we systematically investigated a correlation between device performance and Fc concentration in the electrolyte layer. The optimized Fc concentration is 0.05 M, at which the coloration efficiency ( η ) was ∼34.3 cm 2 C −1 . Furthermore, adding Fc to the electrolyte results in better cyclic (coloration/bleaching) stability.